Proses Penciptaan Tari Dharma Vanita - Triraksa, Ummi (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research aims to introduce the creative process of creating the dance work Dharma Vanita, which revolves around the struggles of women as mothers or wives in assisting their husbands in meeting the needs of their children. The focus is on the process of creating the Dharma Vanita dance and its choreographic form. To approach this issue, reference is made to the theories of Alma M. Hawkins and Sumandiyo Hadi, where Sumandiyo Hadi’s book identifies 10 elements consisting of movement, space, musical accompaniment, title, theme, dance genre, number of dancers, costume and makeup, lighting, and props. The research method used is the moving from within research approach, data collected through observation and literature study. The results of this research point to the creative process and choreographic form in the dance work that produces traditional elements.